2020
DOI: 10.11591/ijece.v10i2.pp1229-1238
|View full text |Cite
|
Sign up to set email alerts
|

The development of a wireless LCP-based intracranial pressure sensor for traumatic brain injury patients

Abstract: Raised intracranial pressure (ICP) in traumatic brain injury (TBI) patients can lead to death. ICP measurement is required to monitor the condition of a patient and to inform TBI treatment. This work presents a new wireless liquid crystal polymer (LCP) based ICP sensor. The sensor is designed with the purpose of measuring ICP and wirelessly transmitting the signal to an external monitoring unit. The sensor is minimally invasive and biocompatible due to the mechanical design and the use of LCP. A prototype sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The low moisture permeability, chemical inertness, flexibility, and suitability for microfabrication of LCPs have enabled the development and demonstration of intracranial pressure sensors (Fig. 1A) (50)(51)(52) and intraocular pressure sensors (53,54). In addition, Simonov et al reported the use of LCP for an adaptive intraocular lens with a superior accommodative power of +2.5 diopter, when compared to the majority of existing single-power accommodating intraocular lens (55).…”
Section: Lcps For Sensors and Devicesmentioning
confidence: 99%
“…The low moisture permeability, chemical inertness, flexibility, and suitability for microfabrication of LCPs have enabled the development and demonstration of intracranial pressure sensors (Fig. 1A) (50)(51)(52) and intraocular pressure sensors (53,54). In addition, Simonov et al reported the use of LCP for an adaptive intraocular lens with a superior accommodative power of +2.5 diopter, when compared to the majority of existing single-power accommodating intraocular lens (55).…”
Section: Lcps For Sensors and Devicesmentioning
confidence: 99%
“…This property of the MEMS switch can be applied to radio frequencies (RF), hence the name RF-MEMS switch [5]. For example, RF-MEMS filters and resonators are intended for applications such as duplex filters, RX&TX band filters, global positioning system (GPS) filters, VCOs, reconfigurable antennas and reference oscillators [6]- [8]. The other application field is RF-MEMS switches, which are very interesting for multi-system phones and with IoT [9], [10].…”
Section: Introductionmentioning
confidence: 99%